Exploring the Impact of the SOLE (Self Organized Learning Environment) Model on Student Response and HOTS - Abu, Siti Hayatun Nur; Bundu, Patta; Haling, Abdul (Journal of Educational Science and Technology (EST), 2024)
This study aims to determine the impact of the application of the SOLE learning model in terms of student response to learning and students' thinking skills after going through SOLE learning. This study is pre-experimental research using a one-shot case study design involving one independent variable, namely the SOLE Model, and dependent variables, namely student response and student HOTS ability. The source of the research data was 60 students as a sample. Data collection techniques include questionnaires and tests. Questionnaire to determine the usefulness of the SOLE model based on student responses. Test instruments are used to determine a student's HOTS profile. The data obtained are analyzed descriptively, scored, and categorized. The results showed that students' responses to SOLE learning were in a good category, which means that SOLE learning is beneficial for students. The HOTS test results showed that  3% of students had sufficient HOTS profiles, 80% of students had good HOTS profiles, and 17% of students had excellent HOTS profiles.